Ultrasonographic, endoscopic and histological appearance of the caecum in clinically healthy cats. Issue 2 (February 2017) - Hahn, Harriet; Freiche, Valérie; Baril, Aurélie; Charpentier, Julie; Desquilbet, Loïc; Le Poder, Sophie; Servely, Jean-Luc; Laloy, Eve; Pey, Pascaline
Objectives: The aim of the study was to describe the ultrasonographic and endoscopic appearance and characteristics of the caecum in asymptomatic cats, and to correlate these findings with histology. Methods: Ex vivo ultrasonographic and histologic evaluations of a fresh caecum were initially performed. Then, 20 asymptomatic cats, privately owned or originating from a reproductive colony, were recruited. All cats had an ultrasonographic examination of the ileocaecocolic junction, where the thickness of the caecal wall, ileocolic lymph nodes and the echogenicity of the local fat were assessed. They all underwent a colonoscopy with a macroscopic assessment of the mucosa and biopsies for histology. Results: An ultrasonographic hypoechoic nodular inner layer, which corresponded to the coalescence of multiple lymphoid follicles originating from the submucosa and protruding in the mucosa on histology, was visible in all parts of the caecum. The combined mucosa and submucosa was measured ultrasonographically and defined as the follicular layer. Although all cats were asymptomatic, 3/19 cats showed mild caecal inflammation on histology. The most discriminatory ultrasonographic parameter in assessing this subclinical inflammation was the thickness of the follicular layer at the entrance of the caecum, with a cut-off value of 2.0 mm. All cats (20/20) showed some degree of macroscopic 'dimpling' of the caecal mucosa on endoscopy. Conclusions and relevance: Lymphoid follicles in the caecal mucosa and submucosa constitute a unique follicular layer on ultrasound. In asymptomatic cats, a subtle, non-clinically relevant inflammation may exist and this is correlated with an increased thickness of the follicular layer on ultrasound. On endoscopy, a 'dimpled aspect' to the caecal mucosa is a normal finding in the asymptomatic cat.